Kesesuaian Lahan Padi Sawah di Desa Bumi Rapak dan Desa Selangkau Kabupaten Kutai Timur: Land Suitability of Rice Fields in Bumi Rapak Village and Selangkau Village East Kutai Regency - Surya Darma (Jurnal Ilmu Tanah dan Lingkungan, 2022)
The major production of paddy fields is grain, which produces rice as the principal ingredient of Indonesian people’s food. The characteristics of the land that can be evaluated or not suitable and the limiting factors influence the suitability of land for lowland rice. East Kutai Regency in East Kalimantan Province has a fairly large paddy field as a grain producer in Bumi Rapak Village and Selangkau Village. The research objectives to understand and explore the suitability class of paddy fields in Bumi Rapak Village, Selangkau Village, and the principal limiting factors. The method applied by matching the growing requirements of lowland rice with the characteristics of paddy fields. We prove that the low availability of P2O5 nutrients so that the actual land suitability class for lowland rice is marginally suitable (S3) and sub-class S3n; the productivity is only 4.54 tons (ha-1). Improvement efforts carried out by low-to-moderate inputs with the application of SP-36 fertilizer at a dose of 100 kg (ha-1) per growing season, the suitability class increases of quite appropriate (S2) and the S2n sub-class expected to increase productivity to 5.00-6.00 tons (ha-1).